PENGEMBANGAN KOMPETENSI PUSTAKAWAN AKADEMIK PERGURUAN TINGGI BERBASIS UTAUT DAN INTEGRITAS AKADEMIK - Dewi Khrisna Sawitri (Pustakaloka, 2026)
Students and lecturers use the digital environment to access various information sources to produce a range of academic outputs. This condition also encourages increasing acceptance of Generative Artificial Intelligence (GAI). Various academic outputs are currently produced with GAI's support, especially by students accustomed to using this technology in academic activities. This study aims to: (1) analyze the acceptance and use of Generative Artificial Intelligence by students, (2) develop a librarian competency model that supports academic integrity in managing academic outputs in the GAI era. This study uses a mixed-method approach implemented in two stages. First, the researcher distributed a survey to 376 participants to obtain an overview of students' acceptance and use of GAI. The second stage was carried out through observations and interviews with six informants who manage faculty libraries and the central library. In addition, a literature review was also conducted to identify librarian competencies relevant to the use of GAI in the academic environment. The study's results recommend a librarian competency model that includes the hard and soft skills needed to support the responsible use of GAI and aligns with the principles of academic integrity in managing academic outputs.